IImproving The Quality of Human Resources Through Islamic Education - Suherman, Aris; Rosviana, Mohammad Irfan (IAIN Syekh Nurjati Cirebon, 2025)
Education Is the interaction between humans and their environment, including the natural environment and human environment. In this interaction humans are not only the result of interaction with nature and with fellow humans, but the results of the development of optimal human potential in accordance with a room that is open for the development of innovation and creativity. Islamic education is expected to be more developed so that Islamic Education Institutions have their own attraction, because it has a more outward and global dimension. The process of improving the quality of human resources requires a variety of prerequisites in their implementation, including the environment of human life should provide opportunities for the development of students to develop in accordance with the potential available to them. Islamic education, in spiritual and moral growth will be able to help individuals strengthen their faith, creed and recognition of Allah SWT, through law, morals and religious teachings, thus students in carrying out the guidance of faith in God and a deep understanding of the teachings of religion and its value in life in its behavior, and its relationship with God with fellow human beings and all creatures, will reinforce the importance of moral education and spirituality in facing globalization. Keywords: Quality of HR, Islamic Education